Subconscious Manipulation of Pain Expectation Can Modulate Cortical Nociceptive Processing - Lewis, GN; Leys, A; Rice, DA; McNair, PJ (John Wiley & Sons, Inc., 2015)
To determine whether manipulation of the expectation of pain inhibition can enhance the efficacy of conditioned pain modulation in healthy participants Methods: A conditioned pain modulation paradigm was used to investigate the effect of psychological manipulation of expectation on pain inhibition. In 19 healthy men, the lower limb nociceptive flexion reflex was elicited in isolation (test stimulus) and during application of 2 forms of conditioning stimuli. Following application of the first conditioning stimulus (CS1), the participants were informed that the subsequent conditioning stimulus (CS2) would elicit a greater amount of inhibition of test pain compared with the first. Lower limb flexion reflex size, perceived pain ratings of the test stimulus, and ratings of expected pain modulation were obtained for both test and conditioning protocols. Results: The inhibition of perceived pain was significantly greater with CS2 compared with CS1; however, there was no significant difference in inhibition of nociceptive flexion reflex size or the participant's reported expectation of pain modulation between the 2 conditioning stimuli. Discussion: As perceived pain inhibition was enhanced but flexion reflex size unchanged following the intervention, we suggest that the intervention gave rise to an inhibition of ascending nociceptive information at a supraspinal level resulting in reduced pain perception without influencing spinal level processing of nociceptive input. The finding that conditioned pain modulation can be enhanced is of relevance to clinical pain populations who commonly show impaired inhibition.
Keywords: Conditioned pain modulation; Expectation; Flexion reflex; Psychology